Improving spaces for women first responders: A grounded theory on gender equity - Kelly B. Gregory; John G. Mielke; Elena Neiterman (PLoS ONE, 2025)
Emergency response work has historically been performed by men and thus designed with them in mind; however, during the past few decades, increasing numbers of women are conducting this work. Despite growing participation, research suggests women first responders continue to face unsupportive workplace structures and cultures. This study explored the occupational experiences of women who work as firefighters, police officers, and paramedics from Southern Ontario, Canada. Semi-structured interviews conducted with this population (n = 20) focused on resiliency and stress, diversity and inclusion, and gender and the role of professional identity. Constructivist grounded theory guided analysis and cross-profession comparisons. Participants described significant improvements to women’s inclusion in first response work, however, they also identified continuing challenges. While some environments were described as highly supportive, many women still faced sexism and glass ceilings. Despite persisting obstacles, participants were deeply passionate about their work, and actively encouraged other women to join the field. Study results suggest that future advances can be encouraged by addressing the need for improved access to uniforms and equipment, on-the-job training to address barriers to promotions, flexible scheduling and childcare supports, and legislating equity, diversity, and inclusion training for all leaders and workers in the first responder community.